Six-year outcomes in neovascular age-related macular degeneration with ranibizumab - Jacob, Julie (Int J Ophthalmol, 2017)
AIM: To evaluate the outcomes of ≥6y ranibizumab therapy in neovascular age-related macular degeneration (AMD). METHODS: HELIX was a retrospective, observational effectiveness study using medical records of patients treated in three clinics in Belgium. Patients had neovascular AMD and were initially treated with intravitreal ranibizumab (0.5 mg) between November 1, 2007 and October 31, 2008, had ≥6y of data available, and were treated on an ongoing, as-needed basis. Outcomes included best-corrected visual acuity (BCVA) and central retinal thickness (CRT). RESULTS: The sample consisted of 88 eyes from 69 patients. Mean age was 76.4±6.5y, most patients were female (62.3%). Most eyes (62.5%) were treatment-naive, 33 previously treated eyes had received predominantly other anti-vascular endothelial growth factor agents and verteporfin. Mean baseline BCVA was 57.4±12.7 ETDRS letters and CRT was 291.5±86.1 μm. On average, patients received 20.6±11.9 ranibizumab injections over the ≥6y. Intervals between injections were on average 12.7±16.1wk. Mean change in BCVA from baseline to last observation for the sample was less than one letter (-0.9±17.3 letters), with an average loss of -3.2±15.6 letters in previously treated eyes versus a gain of 0.6±18.4 letters in treatment-naïve eyes. When considering a loss of <15 letters over 6y as stabilization of disease, 75.9% of all eyes showed a positive (improvement or stabilization) outcome. Mean change in CRT from baseline to last observation for the sample was -26.9±148.4 μm with the greatest reduction observed in treatment-naive eyes. CONCLUSION: This retrospective study of 69 neovascular AMD patients treated for ≥6y with ranibizumab demonstrates long-term visual stabilization. In light of the natural evolution of the disease, these data confirm that ranibizumab is effective long-term under real-world conditions of heterogeneity of patients, clinicians, and centers.